Probing sterile neutrino freeze-in at stronger coupling - Niko Koivunen; Oleg Lebedev; Martti Raidal (European Physical Journal C: Particles and Fields)
Abstract The regime of dark matter (DM) freeze-in at stronger coupling interpolates between freeze-in and freeze-out. It relies on Boltzmann-suppressed dark matter production, implying that the Standard Model bath temperature never exceeds the dark matter mass. In this work, we study this regime in the context of sterile neutrino dark matter, which can be sufficiently long-lived for a tiny sterile-active mixing. The sterile neutrino is assumed to couple to a real singlet scalar, providing for a thermal production mechanism of the former. We find that DM mass can range from GeV to tens of TeV consistently with all the constraints. The most interesting aspect of the consequent freeze-in phenomenology is that the sterile neutrino dark matter can be probed efficiently by both direct detection experiments and invisible Higgs decay at the LHC.